2006
DOI: 10.1364/josaa.23.002061
|View full text |Cite
|
Sign up to set email alerts
|

Direct transformation of Zernike eye aberration coefficients between scaled, rotated, and/or displaced pupils

Abstract: In eye aberrometry it is often necessary to transform the aberration coefficients in order to express them in a scaled, rotated, and/or displaced pupil. This is usually done by applying to the original coefficients vector a set of matrices accounting for each elementary transformation. We describe an equivalent algebraic approach that allows us to perform this conversion in a single step and in a straightforward way. This approach can be applied to any particular definition, normalization, and ordering of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 5 publications
2
51
0
Order By: Relevance
“…Coupling effects between different high-order aberration terms and between high-order-aberrations (HOAs) and manifest refraction have been found, [44][45][46] for example, between defocus and spherical aberration, or between third-order aberrations and low-order terms, between spherical aberration and coma, or between secondary and primary astigmatisms. These interactions may provide some relative visual benefits 47 but may as well contribute as sources of uncertainty in the conversion of wavefront aberration maps to refractive prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Coupling effects between different high-order aberration terms and between high-order-aberrations (HOAs) and manifest refraction have been found, [44][45][46] for example, between defocus and spherical aberration, or between third-order aberrations and low-order terms, between spherical aberration and coma, or between secondary and primary astigmatisms. These interactions may provide some relative visual benefits 47 but may as well contribute as sources of uncertainty in the conversion of wavefront aberration maps to refractive prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a Monte Carlo simulation was performed for simulating the treatment decentration in our study. In addition, the translation and rotation of ablation profile could be simulated theoretically by wavefront transformation [13].…”
Section: Introductionmentioning
confidence: 99%
“…While there exist various publications dealing with analytical scaling transformations to a different pupil size [14][15][16][17][18][19][20][21], rotating the pupil [14,[20][21][22], displacing the pupil [14,15,[20][21][22], or deforming the pupil [21], only a few publications can be found that attempt to treat the wavefront propagation in an analytical way. In [14,23], an analytical method is described to calculate the propagation of a wavefront, but the method is still restricted by some approximations.…”
Section: Introductionmentioning
confidence: 99%